Basis for the judgment of criminal responsibility exemption in cases of insanity - MAZI, Amel (Journal of Human Sciences, 2024)
In spite of the fact that the majority of criminal legislation agrees that insanity is a negation of criminal responsibility, there is disagreement regarding the objective and procedural basis for this exoneration due to insanity. This research paper will elucidate the points of divergence, highlighting the position of Algerian legislators on this matter